Policy, Poverty, and Indigenous Child Welfare: Revisiting the Sixties Scoop - Carneiro, Sarah (2018)
I analyse the Sixties Scoop through the lens of Indigenous and feminist scholarship to contextualize the Scoop within the specific historical, political, and cultural moment of the postwar Canadian “welfare state” during which it was occurring. In the 1960s and 1970s, Canada was attempting to foment a unique “Canadian” identity that became increasingly tied to the values of cultural pluralism and tolerance. During this time, both the state and Indigenous activism questioned where and how Indigenous people would “fit” (or would not fit) into the burgeoning Canadian cultural “mosaic” of the late 20th century. Through an analysis of the 1966/67 federal government report, A Survey of the Contemporary Indians of Canada: Economic, Political, and Educational Needs and Policies (The Hawthorn Report), alongside articles from the Journal – Ontario Association of Children’s Aid Societies (JOACAS), mostly authored by social workers about reserve communities in Northern Ontario during the 1960s and 1970s, I aim to illuminate the intimate relationship between capitalist development, settler colonialism, and patriarchy in postwar Canada. I argue that one of the causes of the Scoop was the inability of governments and Children’s Aid Societies (CAS) administrators and frontline service providers to conceptualize the mass apprehension of Indigenous children from their homes during the 1960s to 1980s as holistically and inextricably connected to the social, political, cultural, and economic aspects of Indigenous people’s lives. M.A.